2009
DOI: 10.1016/j.virusres.2009.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the molecular physiopathology of acute respiratory distress syndrome in severe acute respiratory syndrome patients

Abstract: Acute respiratory distress syndrome (ARDS) is a severe form of acute lung injury. It is a response to various diseases of variable etiology, including SARS-CoV infection. To date, a comprehensive study of the genomic physiopathology of ARDS (and SARS) is lacking, primarily due to the difficulty of finding suitable materials to study the disease process at a tissue level (instead of blood, sputa or swaps). Hereby we attempt to provide such study by analyzing autopsy lung samples from patient who died of SARS an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
85
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(91 citation statements)
references
References 31 publications
6
85
0
Order By: Relevance
“…Nonetheless, these overlapping mRNAs and lncRNAs validate our experimental setup and form ideal targets to be further investigated in the context of HIV infection. For instance, a well-known and characterized lncRNA, MALAT1 (lnc-SCYL1-1) is found in both datasets and is already linked to viral infection43. In addition, in HIV infected individuals MALAT1 is shown as a potential biomarker44.…”
Section: Discussionmentioning
confidence: 92%
“…Nonetheless, these overlapping mRNAs and lncRNAs validate our experimental setup and form ideal targets to be further investigated in the context of HIV infection. For instance, a well-known and characterized lncRNA, MALAT1 (lnc-SCYL1-1) is found in both datasets and is already linked to viral infection43. In addition, in HIV infected individuals MALAT1 is shown as a potential biomarker44.…”
Section: Discussionmentioning
confidence: 92%
“…Consistent with ARDS progression, the primary targets of SARS-CoV infection are ciliated cells of the airway epithelium and alveolar Type II pneumocytes [12,13]. ARDS is also associated with the induction of inflammatory cytokines including IL-1, IL-6, IL-8, CXCL-10, and TNFa, many of which were highly expressed in the lungs of SARS patients [14,15]. In many viral infections the antiviral cytokine Interferon (IFN) acts not only to control viral infections, but also to program the adaptive immune response to promote viral clearance [16].…”
Section: Sars-cov: the First Viral Pandemic Of The New Milleniummentioning
confidence: 96%
“…Therefore, the clinical deterioration of SARS-CoV infection may result from a combination of direct virus-induced cytopathic effects and immunopathology induced by a hyper-cytokinemia or a "cytokine-storm." Studies of the changes in cytokine/chemokine profiles during SARS-CoV infection revealed increased levels of circulating cytokines, such as tumor necrosis factor α (TNF-α), CXCL-10, interleukin-6 (IL-6), and IL-8, likelycontributed to the poor prognosis in SARS-CoV infections 15. …”
mentioning
confidence: 99%